Reporting Outcomes and Outcome Measures in Digital Replantation: A Systematic Review - Moltaji, Syena; Gallo, Matteo; Wong, Chloe; Murphy, Jessica; Gallo, Lucas; Waltho, Daniel; Copeland, Andrea; Karpinski, Marta; Mowakket, Sadek; Duku, Eric; Thoma, Achilleas; On Behalf of the McMaster University Plastic Surgery Core Outcome Sets & Measures Adapted to Surgery Working Group (Journal of Hand and Microsurgery, 2020)
Introduction There is a lack of consensus on what the critical outcomes in replantation are and how best to measure them. This review aims to identify all reported outcomes and respective outcome measures used in digital replantation.Materials and Methods Randomized controlled trials, cohort studies, and single-arm observational studies of adults undergoing replantation with at least one well-described outcome or outcome measure were identified. Primary outcomes were classified into six domains, and outcome measures were classified into eight domains. The clinimetric properties were identified and reported. A total of 56 observational studies met the inclusion criteria.Results In total, 29 continuous and 29 categorical outcomes were identified, and 87 scales and instruments were identified. The most frequently used outcomes were survival of replanted digit, sensation, and time in hospital. Outcomes and measures were most variable in domains of viability, quality of life, and motor function. Only eight measures used across these domains were validated and proven reliable.Conclusion Lack of consensus creates an obstacle to reporting, understanding, and comparing the effectiveness of various replantation strategies.
Keywords: digital replantation; outcome measures; outcomes